Micro‐ and nanomotors in biomedical applications - Xiangyu Meng; Yuqi Tang; Quan Li (Responsive Materials)
Abstract Micro‐ and nanomotors (MNMs) are minuscule devices capable of independently navigating and executing designated functions within micro‐ and nanoscale domains. MNMs are emerging as a promising category of drug delivery vehicles, capable of transforming disease microenvironment chemical or external energy into mechanical force, facilitating their self‐propelled motion. In recent years, MNMs have showcased immense promise in the field of biomedicine, especially in the treatment of diseases. This review first explores the design principles of the propulsion and operation of MNMs, and then highlights the remarkable capabilities of MNMs in various biomedical applications, including cardiovascular disease, gastrointestinal disease, wound sealing and hemostasis, central nervous system disease, bladder disease, antimicrobial applications, and cancer therapy. Finally, the review discusses the challenges and future opportunities in the biomedical application of MNMs.